Proteolytic Bacillus spp. associated with tannery industries: Conventional and molecular identification - Saha, Mihir Lal; Khan, Tahsin; Kamal, Md Mostafa; Islam, Mohammad Nurul (Bangladesh Journal of Botany, 2018)
Samples collected from different stages of the tannery industry were found to be alkaline (pH 7.52 to 12.11). A good number of bacteria were found to be associated with the samples. The bacterial count ranged in between 1.34×105 to 3.44×105 cfu/ml and 1.04×105 to 6×105 cfu/ml on nutrient agar (NA) and peptone yeast extract glucose agar (PYG) medium, respectively. The maximum bacterial count was observed in bating stage while the minimum count was in the deliming stage. Primarily, 70 isolates were selected based on their different colonial morphology. After heat shock test 27 isolates were finally selected for identification and proteolytic potential. All the selected isolates were the members of different species of the genus Bacillus. The conventionally identified species were B. stearothermophilus (9), B. subtilis (4), B. brevis (3), B. pumilus (3), B. alcalophilus (2), B. badius (2), B. firmus (2) and B. lentus (2). Four important proteolytic isolates of Bacillus were selected for molecular identification. The isolates were confirmed as Bacillus subtilis strain B20 (L/P/2/1), B. subtilis strain PB18 (D/P/3/1), Bacillus sp. strain BVC38 (D/P/3′/2) and B. amyloliqefaciens strain Egy25 (B/N/3′/1). Except B/N/3′/1 all the conventional identification was in accordance with the molecular identification as the isolate B/N/3′/1 was conventionally identified as B. pumilus (B/N/3′/1). All the isolates showed positive proteolytic activities on skim milk agar and the zone ratio was in between 2.61 ± 0.44 and 6.42 ± 0.95. These isolates could be commercially utilized in the tannery and detergent industries for their proteolytic activity.